2023
DOI: 10.3390/jcm12196312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Motor Evoked Potentials Neuromonitoring Following Pre- and Postoperative Transcranial Magnetic Stimulation and Intraoperative Electrical Stimulation in Patients Undergoing Surgical Correction of Idiopathic Scoliosis

Przemysław Daroszewski,
Juliusz Huber,
Katarzyna Kaczmarek
et al.

Abstract: The relationships between the results of pre- and intraoperative motor evoked potential recordings during neuromonitoring and whether idiopathic scoliosis (IS) surgical correction improves the spinal efferent transmission have not been specified in detail. This study aims to compare the results of surface-recorded electromyography (EMG), electroneurography (ENG, M, and F-waves), and especially motor evoked potential (MEP) recordings from tibialis anterior muscle (TA) bilaterally in 353 girls with right idiopat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 64 publications
4
10
0
Order By: Relevance
“…The results of this study in patients surgically treated for idiopathic scoliosis confirmed the previous findings in [7], namely, that the transmission of efferent neural impulses in the spinal cord tracts and within the fibers of the peripheral nervous system slightly improves immediately after the surgical correction of scoliosis. Moreover, we ascertained the further normalization of the motor function together with the improvement of TA muscle motor unit recruitment half a year after the surgical treatment in IS patients, in which the mcsEMG parameter values are comparable to those of the normal condition.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The results of this study in patients surgically treated for idiopathic scoliosis confirmed the previous findings in [7], namely, that the transmission of efferent neural impulses in the spinal cord tracts and within the fibers of the peripheral nervous system slightly improves immediately after the surgical correction of scoliosis. Moreover, we ascertained the further normalization of the motor function together with the improvement of TA muscle motor unit recruitment half a year after the surgical treatment in IS patients, in which the mcsEMG parameter values are comparable to those of the normal condition.…”
Section: Discussionsupporting
confidence: 89%
“…All surgical procedures were applied under the control of X-ray C-arm and neuromonitoring navigations (Figure 2(Da,Dc)). Further details regarding the surgical procedures and intraoperative neurophysiological recordings are described elsewhere [7].…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations